THE EFFECT OF TEACHING TECHNIQUE AND GRAMMAR MASTERY TOWARD READING COMPREHENSION AT THE EIGHT GRADE STUDENTS OF JUNIOR HIGH SCHOOL IN PANDEGLANG - Dahlina, Ulinuha (Journal of Industrial Engineering & Management Research, 2020)
The purpose of this study was (1) to show the effect of teaching techniques on students’ reading comprehension at the eighth grade students of junior high school in Pandeglang (2) to show the effect of grammar mastery on students’ reading comprehension at the eighth grade students of junior high school in Pandeglang (3) to show the effect teaching techniques and grammar mastery simultaneously toward students’ reading comprehension at the eighth grade students of junior high school in Pandeglang. The research method used was an experimental method with two-way ANOVA analysis. The sample was eighty students of the eighth grade of senior high school Pandeglang and the sampling was done through a qualitative approach, data collection was carried out by means of a test filled with respondents. Data analysis consisted of: descriptive statistical analysis, data analysis requirements test (normality and homogeneity test), and hypothesis testing with two-way ANOVA. The statistical test used probability test (Sig.). This research was conducted from April to July 2015. The results showed that there is an effect of teaching techniques on students’ reading comprehension. This is proved by the Sig. = 0.000 <0.05. There is an effect of grammar mastery on students’ reading comprehension, this is evidenced by the Sig. = 0.000 <0.05. There is an effect of teaching techniques and grammar mastery simultaneously on students’ reading comprehension, this is proved by the Sig. = 0.000 <0.05.